Real-time traffic separation in shared ethernet networks: simulation analysis of the h-BEB collision resolution algorithm - Ricardo Moraes (2005)
In this paper, the enhanced collision resolution algorithm, referred as high priority Binary Exponential Backoff (h-BEB) is analyzed. Such algorithm provides high priority traffic separation, enabling the support of real-time communication in shared Ethernet networks. It allows multiple Ethernet standard devices to coexist in the same network segment with one h-BEB enhanced station, imposing higher priority for the transfer of h-BEB related traffic. The simulation analysis shows that the h-BEB algorithm guarantees values for both the average access delay and the related standard deviation, that are significantly smaller for the h-BEB station than for the BEB stations.